2013
DOI: 10.3109/10715762.2013.784965
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine induces COX-2 expression in macrophages through ROS generated by NMDA receptor-calcium signaling pathways

Abstract: Homocysteine (Hcy) at elevated levels is a putative risk factor for many cardiovascular disorders including atherosclerosis. In the present study, we investigated the effect of Hcy on the expression of cyclooxygenase (COX)-2 in murine macrophages and the mechanisms involved. Hcy increased the expression of COX-2 mRNA and protein in dose- and time-dependent manners, but did not affect COX-1 expression. Hcy-induced COX-2 expression was attenuated not only by the calcium chelators, EGTA and BAPTA-AM, but also by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…Recently, we have shown that NMDARs in RBCs show a high degree of basal activity when in the circulation (18). Additionally, glutamate levels within the bone marrow may be regulated by controlled secretion of this amino acid from megakaryocytes and macrophages (3, 22, 32, 39). The close association of bone marrow and glutamatergic nerve endings may further contribute to the alterations in glutamate levels promoting erythropoiesis and increasing RBC production.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have shown that NMDARs in RBCs show a high degree of basal activity when in the circulation (18). Additionally, glutamate levels within the bone marrow may be regulated by controlled secretion of this amino acid from megakaryocytes and macrophages (3, 22, 32, 39). The close association of bone marrow and glutamatergic nerve endings may further contribute to the alterations in glutamate levels promoting erythropoiesis and increasing RBC production.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 In addition to neuronal expression of NMDAR, recent studies showed that NMDAR activity is also present in peripheral tissues, including macrophages, bone marrow and the cardiovascular system. 16,17 The effects of central and peripheral NMDAR are often differentiated using the specific antagonists MK-801 and D-AP5. MK-801 is used to block overall NMDAR activity for its ability to cross the blood-brain barrier 18,19 and D-AP5 is used to study the role of peripheral NMDAR.…”
mentioning
confidence: 99%
“…Hcy induced COX-2 expression in macrophages, hepatic cell, as well as in the primary cultured CN neurons, which was hazardous to the function of cells [14,22,38]. Previous findings showed that the direct application of 2-AG or elevation of endogenous 2-AG by URB602 protects the hippocampal and CN neurons through suppression of cyclooxygenase-2 (COX-2) expression, which is provoked by pro-inflammatory IL-1β and LPS, excitotoxic glutamate and kainic acid and β-amyloid, via a CB1 receptor-dependent NF-κB signaling pathway [12,25,41].…”
Section: Discussionmentioning
confidence: 99%